Vezljivost glagolov védenja v stari cerkveni slovanščini - Grošelj, Robert (Slavistična revija, 2010)
The article deals with the valency of the verbs of knowing, i.e., ouměti, věděti (with its secundary imperfect vědati), znati, in Old Church Slavic. The meaning are elucidated the denotative possibilities given, and they are juxtaposed by meaning and combinatory patterns, which are then treated with a view to their stability and competition with one another. At the end of the paper the combinatory pecularities of the analyzed verbs of knowing are compared.
Keywords: glagol; glagoli védenja; stara cerkvena slovanščina; verb; vezljivost